Seasonal Variation in Microbial Communities in Rhizosphere and Non-Rhizosphere soil of Different Fruit Tree Species in Semiarid Irrigated Conditions of Haryana - Kumar, Dinesh; Dalal, R. P. S.; Kumar, Rakesh; Parshad, Jagdish; Jaipal, Jaipal (International Journal of Bio-resource and Stress Management, 2021)
The present study was undertaken to analyze seasonal variations in microbial communities in different fruit tree orchards (mango, guava, ber, bael, jamun, aonla and sweet orange) during summer, rainy and winter season of 2018-19 under semiarid irrigated ecosystem. In rhizosphere and non-rhizosphere, maximum TBC, PSB and nitrogen fixers were found in mango orchard during summer and rainy season while maximum fungal count in jamun orchard during all the seasons. Maximum actinomycete was counted in guava orchard during summer and winter while in mango during rainy season. In rhizosphere and non-rhizosphere, the total microbial count, phosphate solubilizing bacteria and nitrogen fixers were maximum in rainy season while fungal and actinomycetes count in summer season. The maximum increase in total microbial count, PSB and nitrogen fixers or diazotrophs were found in mango orchard during summer (11.61%, 7.88%, 7.67%) and rainy season (11.16%, 7.57%, 6.93%) respectively, over the control while lowest total bacterial count, phosphate solubilizing bacteria and nitrogen fixers count were observed in ber (20.03%), guava (10.25%) and sweet orange orchard (13.58%). However, maximum increase in fungal count over control was found in jamun orchard during summer (25.77%), rainy (21.83%) and winter season (33.44%). Maximum increase in actinomycetes count over control was found in guava orchard during summer (8.72%) and (9.37%) during winter season. Whereas in mango orchard during rainy (10.71%).